Characteristics and driving forces of spatial and temporal changes of drought in Yuanjiang dry–hot valley area of China based on TVDI - Gu, Zhijia; Zhai, Sennan; Feng, Detai; Xu, Gaohan; Ji, Keke; Wang, Rui; Li, Ao (Frontiers in Environmental Science, 2025)
IntroductionThe Yuanjiang dry–hot valley area of China serves as a vital ecological functional zone and a typical ecologically fragile area, where drought constitutes a significant factor affecting both the ecological environment and agricultural production. Conducting an in–depth analysis of drought variation trends across spatiotemporal scales and exploring its primary driving factors in this region will provide a scientific reference for regional drought monitoring and warning, drought prevention and disaster reduction efforts.MethodsBy analyzing the Temperature Vegetation Dryness Index (TVDI) constructed from the Land Surface Temperature (LST) and Normalized Difference Vegetation Index (NDVI) from 2000 to 2020, combined with Theil–Sen trend analysis method, M–K trend test, stability analysis, Hurst index, and geographic detector, the characteristics, future evolution trends, and influencing factors of drought spatiotemporal changes in the Yuanjiang dry–hot valley area were analyzed from a spatiotemporal perspective.ResultsThe results indicated that (1) the average TVDI in the Yuanjiang dry–hot valley area from 2000 to 2020 was 0.67, showing a moderately dry state as a whole, and it was slowly decreasing at a rate of 0.0011 per year, indicating that the drought situation has eased. (2) The TVDI showed a trend of a slow increase in the northwest and a slow decrease in the southeast area, with a relatively high stability. In the future, the TVDI in the northwest of the study area will weakly and continuously increase, while the TVDI in the southeast will weakly and continuously decrease. The future changes are also relatively stable. (3) In the Yuanjiang dry–hot valley area, potential evapotranspiration, precipitation, and temperature are key factors influencing TVDI. Among these, potential evapotranspiration is the most significant factor, with a q value of 0.3768. The interaction effects between factors exceed the influence of any single factor, particularly the interaction between potential evapotranspiration and GDP, which shows the strongest effect (q value is 0.490).DiscussionThe results in the study indicated that the future trend of drought changes was highly uncertain. The future changes in drought conditions still require continuous attention. Cultivated land and woodland exhibited the highest contribution rate to TVDI. Natural factors exert a strong influence on drought conditions, while the impact of human factors remains less pronounced.